Entrepreneurial Marketing Strategies in the Tourism Industry - Widodo, Aghnia Kamila; Dewi, Yuli Kartika; Yahya, Nashwa Aulia (Jurnal Entrepreneur dan Entrepreneurship, 2026)
This study examined how entrepreneurial digital marketing through YouTube travel influencers influences visit intention among Generation Z and Millennial tourists in Indonesia, with trust acting as an underlying psychological mechanism. The study addressed the growing role of influencers as digital entrepreneurs who create value and shape tourism-related decision-making. A quantitative research design was employed using survey data collected from 138 Generation Z and Millennial respondents in Indonesia who had prior travel experience and exposure to YouTube travel influencer content. Data were analyzed using Partial Least Squares - Structural Equation Modeling (PLS-SEM) to test the relationships among homophily, perceived expertise, trust, and visit intention. The findings indicated that homophily and perceived expertise significantly influence trust toward YouTube travel influencers. Homophily emerged as the strongest direct determinant of visit intention, while trust did not exert a significant direct effect. These results demonstrate that social similarity and emotional identification function as key entrepreneurial mechanisms in influencer-based tourism marketing, rather than purely rational or informational factors. The study characterizes YouTube travel influencers as digital entrepreneurs who generate marketing value through social similarity and perceived knowledge from an entrepreneurial marketing viewpoint.